Autism in Glasgow: cumulative incidence and the effects of referral age, deprivation and geographical location. Issue 5 (1st November 2011) - Campbell, M.; Reynolds, L.; Cunningham, J.; Minnis, H.; Gillberg, C.
Abstract Background Referrals to the Greater Glasgow Community Autism Team (CAT) made before the child's sixth birthday were analysed to obtain an estimation of the proportion of children in Greater Glasgow with childhood autism and investigate whether there were any variations in diagnosis rates, or in age at referral and diagnosis, depending on deprivation or geographical location. Methods An analysis was made of the database recording referrals to Greater Glasgow CAT, between 2004 and 2007 inclusive, of children referred by age 6 years, comprising 584 cases. Cumulative incidence was calculated for childhood autism. Ages at referral and diagnosis were also analysed. Results For this subset of children, there were 246 diagnosed cases of childhood autism, a cumulative incidence from 2004 until 2007 of 11.1 per year per 10 000 children aged 0–6 years. Of children with an eventual diagnosis of autism by age 6, 72% were referred by the age of 4 years. Deprivation was found to have an association with referral and diagnostic rates, with higher rates seen in the most deprived. There was geographical variation in the cumulative incidence of autism. Conclusion Given that the populations were not known to differ in any manner that would lead to a true variation, the geographical variation in the cumulative incidence of autism in children up to 6 years in Greater Glasgow observed in this study is likely to represent differences in the care pathway between areas. Such differences may also explain the observed association with deprivation. Reasons for the variation are being explored.